Gambaran Kelistrikan Jantung Anak Babi pada Kondisi Renjatan dengan Resusitasi Hipervolemik Menggunakan Cairan Kristaloid Natrium Chlorida 0,9% - Gunanti, Gunanti; Soesatyoratih, Soesatyoratih; Pudjiadi, Antonius H; Purba, Melpa Susanti; Kusumanto, Galih Satria (Jurnal Veteriner, 2020)
This study aimed to determine the effect of resuscitation and hypervolemic conditions on shocked piglet’s heart electrical system. Animal models that were used in this study are 5 healthy castrated piglets. The piglet’s blood were withdrawn until the mean arterial pressure dropped about 20 % from the baseline condition to make a hypovolemic shock condition. When the piglets reached the hypovolemic shock state, fluid resuscitation using crystalloid (NaCl 0.9 %) as much as 40 ml/kg were given using a 50 ml syringe through the jugular vein. ECG examination were performed before surgery and when it reached the hypervolemic state after being resuscitated. The ECG results indicate no apparent change in cardiac performance due to the absence of ECG waveform changes from waveforms during normal conditions. In conclusion, crystalloid fluid resuscitation (NaCl 0.9 %) until hypervolemic condition does not interfere with cardiac performance.